Conflict Analysis of the Main Character in the Short Story "The Yellow Wallpaper" by Charlotte Perkins Gilman - Mutmainna Adam, Fauzia; Laya, Rachmi; Podungge, Rusni (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
This research intends to analyze the impact of internal and external conflicts on the main character in "The Yellow Wallpaper" and to understand how these conflicts shape the character's psychological state and overall narrative development throughout the story. This research employed the qualitative method and structuralism approach in discovering internal and external conflicts showed by the character in "The Yellow Wallpaper". The data for this research is a short story with the title â€œThe Yellow Wallpaperâ€, written by Charlotte Perkins Gilman. Through the exploration of internal conflicts, such as the main characterâ€™sstruggle with her own desires and perceptions, and external conflicts, including her interactions with her husband and societal expectations, it becomes evident that these conflicts profoundly impact the main character's psyche and overall well-being. By examining the interplay between internal and external conflicts, this research sheds light on the complex dynamics at play within the narrative and underscores the significance of understanding how conflicts, both internal and external, can profoundly impact an individual's mental situation and welfare.